The curse of taxonomic uncertainty in biogeographical studies of free-living terrestrial protists: a case study of testate amoebae from Amsterdam Island - Heger, Thierry J; Mitchell, Edward; Ledeganck, Pieter; Vincke, Sofie; Van de Vijver, Bart; Beyens, Louis (My University, 2009)
Aim A current debate in microbial biogeography contrasts two views concerning the distribution of free-living microorganisms. The first view assumes a ubiquitous distribution, while the second assumes that at least some species have limited geographical distributions. We tested for limited geographical distributions by identifying testate amoebae morphospecies from an extremely remote oceanic island where the potential for endemism is high. Location Amsterdam Island, Indian Ocean. Methods Sixty moss and water samples collected from the top of the volcano to the lowland were investigated for their testate amoeba content. Due to taxonomic uncertainties among the Argynnia (Nebela) dentistoma species complex (including A. antarctica), we also performed light and scanning electron microscopy investigations on the shell ultrastructure and biometric analyses on several specimens of this taxon. Results We identified a total of 43 testate amoeba taxa belonging to 15 genera. Only four testate amoeba taxa had previously been recorded on this island. Testate amoeba communities of Amsterdam Island are dominated by cosmopolitan ubiquitous euglyphid taxa such as Trinema lineare, Assulina muscorum and Corythion dubium. The length and width ranges for Argynnia dentistoma on Amsterdam Island overlap with other records of this species and of A. antarctica, suggesting that A. antarctica is not a distinct taxon. Main conclusions Although Amsterdam Island is among the most remote islands in the world, an extensive inventory of testate amoeba morphospecies provided no clear evidence for endemism. On the one hand, our detailed morphometric analysis of the A. dentistoma complex revealed that A. antarctica, a morphospecies previously suggested to display endemism, cannot be confidently distinguished from the cosmopolitan morphospecies A. dentistoma. On the other hand, five morphotaxa could not be identified with certainty and might represent new species, potentially with limited distribution. These examples illustrate how taxonomic uncertainties undermine biogeographical studies of testate amoebae. In order to allow better interpretation of morphology-based testate amoeba distribution data, an assessment of genetic diversity among and within morphotaxa in relation to geographical distance for some common testate amoebae should be given high priority.
Keywords: Amsterdam Island; biogeography; cosmopolitan distribution; endemism; Indian Ocean; microorganisms; taxonomy; testate amoebae; DWELLING TESTACEAN FAUNA; SOUTH-GEORGIA; RHIZOPODA-TESTACEA; LA; POSSESSION; INDIAN-OCEAN; DIATOM FLORA; DIVERSITY; PROTOZOA; MICROORGANISMS; ARCELLINIDA